The Addition Of Effective Microrganism 4 And Charcoal Husk To Biofilter In Domestic Wastewater Treatment In Makassar. (February 2019) - Natsir, M F; Ibrahim, E; Arsunan, A.A; Mallongi, A; Selomo, M
Abstract: Liquid waste is a potential source of water pollution as it contains a fairly high compound: chemical compounds and pathogenic microorganisms that are harmful to health. Therefore, it is necessary to be processed first before discharged to waterbody. This study aims to determine the effectiveness of the addition of EM4 and charcoal husk to biofilter in reducing BOD, TSS, and NH3 levels in domestic wastewater. This experimental research was conducted by using Pretest-Posttest design in several steps, including literature review, biofilter construction, media setup, and biofilter examination as the main research. The basic principle of the biofilter was using microorganism to disentangle the compound and pollutant in the wastewater. The microorganisms grew to attach to the media surface and formed a biofilm layer. The results revealed that after biofilm growing for 28 days, there was a difference in the level of BOD, TSS, and NH3 before and after the processing. The average of BOD level decreased for 45, 01% (258, 134 mg/l to 130, 96 mg/l), meanwhile, the average of TSS level decrease by 73, 15% (116, 6 mg/l to 29, 8 mg/l) and the NH3 level reached 37, 96% (0, 162 mg/l to 0, 10 mg/l). Biofilter had been able to reduce TSS and NH3 levels by specified quality standards, while for BOD parameter were still above the quality standard.